2019
DOI: 10.1530/eje-18-0602
|View full text |Cite
|
Sign up to set email alerts
|

Early menopause and premature ovarian insufficiency are associated with increased risk of type 2 diabetes: a systematic review and meta-analysis

Abstract: Objective/Design Menopausal transition has been associated with a derangement of glucose metabolism. However, it is not known if early menopause (EM, defined as age at menopause <45 years) or premature ovarian insufficiency (POI, defined as age at menopause <40 years) are associated with increased risk of type 2 diabetes mellitus (T2DM). To systematically investigate and meta-analyze the best evidence regarding the association of age at menopause with the risk of T2DM. Methods A comprehensive search wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 48 publications
(126 reference statements)
1
74
0
1
Order By: Relevance
“…The protective role of endogenous oestrogens in women is evidenced by the deleterious impact of the menopause on body composition and glucose homeostasis, leading to an increased incidence of metabolic disorders vs premenopausal women [12]. Early menopause and premature ovarian insufficiency are associated with an increased risk of type 2 diabetes as compared with premenopausal women, while a 21-35% reduction in diabetes incidence has been reported in menopausal women receiving oestrogen-based hormonal therapy vs placebo [13][14][15]. Further demonstrating the contribution of the oestrogen pathway to diabetes susceptibility in humans, rare loss-of-function mutations in the gene encoding either aromatase (the enzyme that converts androgens into oestrogens) or oestrogen receptor α (ERα) result in dysmetabolic phenotypes in individuals of both sexes [16].…”
Section: A Critical Role For Sex Steroid Hormones In Diabetes Susceptmentioning
confidence: 99%
“…The protective role of endogenous oestrogens in women is evidenced by the deleterious impact of the menopause on body composition and glucose homeostasis, leading to an increased incidence of metabolic disorders vs premenopausal women [12]. Early menopause and premature ovarian insufficiency are associated with an increased risk of type 2 diabetes as compared with premenopausal women, while a 21-35% reduction in diabetes incidence has been reported in menopausal women receiving oestrogen-based hormonal therapy vs placebo [13][14][15]. Further demonstrating the contribution of the oestrogen pathway to diabetes susceptibility in humans, rare loss-of-function mutations in the gene encoding either aromatase (the enzyme that converts androgens into oestrogens) or oestrogen receptor α (ERα) result in dysmetabolic phenotypes in individuals of both sexes [16].…”
Section: A Critical Role For Sex Steroid Hormones In Diabetes Susceptmentioning
confidence: 99%
“…Most studies suggest that the menopausal transition [47] or premature menopause [48] is associated with increased risks of developing insulin resistance, the metabolic syndrome, and type 2 diabetes. This may be mediated by metabolically adverse changes in body composition and by the direct effect of estrogens on insulin sensitivity and pancreatic β -cells.…”
Section: Effects Of Endocrine Therapy On Cardiometabolic Outcomesmentioning
confidence: 99%
“…Data from the InterLACE consortium indicate that in the general female population of high-income countries, the prevalence of premature menopause is 2% (range 1-3%) and of early menopause is 7.6% (range 5-10%), suggesting that almost one in 10 women have premature or early menopause [5]. Recent reviews have concluded that premature or early menopause is associated with an increased risk of all-cause mortality, cardiovascular disease, type 2 diabetes, depression, osteoporosis and fracture [6][7][8][9][10][11]. There is some evidence that premature menopause is associated with greater than average cognitive decline in later life [12], but current studies do not support a consistent association between early menopause and dementia risk [13].…”
Section: Introductionmentioning
confidence: 99%